Friday

November 28, 2014

November 28, 2014

Posted by **kat** on Sunday, October 13, 2013 at 10:52pm.

- math -
**Ms. Sue**, Sunday, October 13, 2013 at 10:57pm-[2x-(5x+2)]=2+(2x+7)

3x + 2 = 9 + 2x

3x - 2x = 9 - 2

x = 7

Check:

-14 + 35 + 2 = 9 + 14

23 = 23

- math -
**Reiny**, Sunday, October 13, 2013 at 11:00pmwork the inner brackets first

-[2x-(5x+2)]=2+(2x+7)

-2[2x - 5x -2] = 2 + 2x + 7

-2[-3x - 2] = 9 + 2x

6x + 4 = 9 + 2x

6x - 2x = 9 - 4

4x = 5

x = 5/4

- go with Ms Sue's, scrap mine math -
**Reiny**, Monday, October 14, 2013 at 12:06amshould have put my glasses on !

**Answer this Question**

**Related Questions**

Quick math help - In which step below does a mistake first appear in simplifying...

Algebra - How do I solve for the elimination method: 5x + 3y= -7 and 7x - 2y =13...

math - please - How do we manually calculate the Present Value of annuity step ...

chem - ok my professor lost me when explaining this material so please bare with...

Algebra help - f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is...

Physics - Can someone please show me step by step how to normalize e^-5x in the ...

Trigonometry - I need help proving the following identity: 4(sin^6(x)+cos^6(x...

math - Help please select the approcimate values of x that are solutions to f(x...

ALGEBRA HELP - When solving the equation, what property was used to go from step...

Algebra 1--Step-by-Step - Can someone show me how to solve these step-by-step? ...